APLIKASI TEPUNG UBI JALAR UNGU TERMODIFIKASI PADA PEMBUATAN BOLU - Wirakerti Nugraha, I Wayan; Anom Jambe, Anak Agung GN; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 4 No 2 (2015): Jurnal ITEPA, 2015)
Research on application of purple sweet potato modified flour in cake making aims to obtain the optimum concentration of the use of purple sweet potato modified flour, which the resulting the best characteristics of cake. The experimental design used in this study was a randomized block design, with concentration of purple sweet potato modified flour as follows: 0%, 25%, 50%, 75%, and 100%. Treatment was repeated three times to obtain 15 units experiment. The study states that a concentration of 75% purple sweet potato modified flour has taked a cake with the best characteristics with swelling was 36,90%, moisture content was 29,21%, ash content was 1,79%, fat content was 16,19%, protein content was 9,13%, carbohydrate was 43,68%, anthocyanin total was 0,63 mg/100g, the antioxidant activity was 61,57%, color was liked, flavour was liked, texture was rather like, taste was liked, and overall acceptance was liked.
Keywords: application, purple sweet potato modified flour, cake